Campaign Ethics for the President in the General Election - Rasji, Rasji; Zimah, Amelia Abdullah; Febriany, Febriany; Rusli, Vennia Neshya (CV. Rayyan Dwi Bharata, 2024)
Every five years, Indonesia holds General Elections that are held directly, generally, freely, secretly, honestly, fairly, or commonly known as Luber Jurdil. In the principle of ethics, in politics related to morals, the politics of a country if followed by ethics then a prosperous, just and prosperous nation will be achieved. At this time, campaigns are still widely used to invite commotion by spreading hoaxes. The president has an obligation to maintain neutrality. The president has an obligation to maintain his neutrality during the election campaign. Yesterday's campaign, the President was accused of carrying out a campaign that skewed towards one of the candidate pairs. In this study, juridical normative research was used to see issues related to campaign ethics for the President. When viewed from the context of democracy, the President has the right and freedom as a citizen to participate in the political process, including in election campaigns. As someone who is subject to the rules, the existence of rules regarding the President's right to campaign during the election period, the President must also maintain ethics and moral values outside of the existing legal rules.